The Effect of Profitability and Company Size on Company Value in the Banking Sector Listed on the Indonesia Stock Exchange for the Period 2022–2024 - Jacob William Marriott; Lorina Siregar Sudjiman (Analitika: Journal of Economics, Management, and Business, 2026)
Abstract. This study aims to analyze the effect of profitability and company size on company value in the banking sector listed on the Indonesia Stock Exchange (IDX) for the period 2022–2024. The banking sector was chosen because of its crucial role as the backbone of the national economy and the high transparency of data through audited financial reports and Financial Services Authority (OJK) supervision. The research method used a quantitative approach with purposive sampling technique. The sample consisted of 15 banks in the KBMI 3–4 category that recorded positive profits throughout the research period and had complete financial statement data. Profitability was proxied by Return on Assets (ROA), company size was measured by the natural logarithm of total assets, and company value was proxied by Price to Book Value (PBV). This study employs multiple linear regression analysis with SPSS version 27. Results show that ROA has a significant positive effect on PBV (β = 87.327, p = 0.000), while company size has no significant effect on PBV (β = −0.009, p = 0.948). Simultaneously, both variables explain 63.7% of PBV variation (R² = 0.637, F = 25.372, p = 0.000). These findings confirm that profitability is the dominant factor shaping market perception of banking company value in the post-pandemic economic recovery era of 2022–2024.